Rotaxane‐type hyperbranched polymers from a crown ether host and paraquat guests containing blocking groups. Issue 11 (8th January 2016) - Lee, Minjae; Gibson, Harry W.
ABSTRACT: Rotaxane‐type hyperbranched polymers are synthesized for the first time from A2 B type semi‐rotaxane monomers formed in situ via complexation of bis( m ‐phenylene)‐32‐crown‐10 dimethanol (1 ) and two paraquat ω ‐ n‐ alkylenecarboxylic acid derivatives with tris( p‐t‐ butylphenyl)methylphenylalkylene stoppers (8 and9) . Rotaxane and taco complexes exist in solutions of the hyperbranched polyesters in CD3 CN/CDCl3 as confirmed by NMR spectroscopy, but the taco complexes, which derive from non‐rotaxanated paraquat units, disappear in DMSO‐ d6 . NMR spectroscopy indicates the portion of rotaxanes strongly interlocked by the environment (inner rotaxanes) is larger inHP19, which has longer alkylene spacers, perhaps indicating a higher degree of polymerization. The molecular size increases upon formation of the hyperbranched polymers are confirmed by dynamic light scattering and by viscometry. As with covalent hyperbranched polymers a number of potential applications exist; the unique mechanically linked character and the presence of uncomplexed host and guest moieties foreshadow the use of such systems for their responses to external stimuli with the added benefit of providing molecular recognition sites useful as delivery vehicles. Use of other host‐guest motifs to form the semirotaxane A2 B monomers is possible and complementary systems with higher binding constants will enable efficient syntheses of high molecular weight, mechanically linked hyperbranched polymers. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2016, 54, 1647–1658 Abstract : Supramolecular rotaxane‐type hyperbranched polymers are synthesized from A2 B type semi‐rotaxane monomers formed in situ via complexation of difunctional bis( m ‐phenylene)‐32‐crown‐10 dimethanol and two monofunctional paraquat ω ‐ n‐ alkylenecarboxylic acid derivatives with tris( p‐t‐ butylphenyl)methylphenylalkylene stoppers. The polymers possess hyperbranched structures and properties, which are confirmed by NMR, dynamic light scattering and viscosity studies.